ELECTRONIC CIGARETTE USE AMONG ADOLESCENTS: A SYSTEMATIC REVIEW - Edi Junaidi; Budi Hidayat (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: The innovation of the cigarettes industry leads to evolved into an electric cigarette. US General Surgeon in 2016 reports that 13.5% of junior high school students, 37.7% of high school students and 35.8% of young adolescents in America have used electric cigarettes. This study aims to identify the use of electric cigarette among adolescent Methods: This study utilized systematic reviews using PRISMA (Preferred Reporting Items for Systematic Reviews & Meta-Analyzes) to identify all published literature using relevant keywords. The selection process is based on the literature of which the population is human, published in the last 5 years, and there is a complete text form, then selected back by title and abstract. The journal used is the selected journal based on the inclusion and exclusion criteria. Results: Electric cigarettes are used by adolescents influence through social media or commercial advertisement. One type of electric cigarette that is widely used is the Electronic Vapor Product (EVP) that can easily to obtain from retail stores, kiosks, malls, and the internet. Electric cigarette users were led to increasing the symptoms of bronchitis and asthma in adolescents. Conclusions: The use of electric cigarettes in adolescents has increased mainly among male adolescents. The current study revealed the use of electronic cigarette was influenced by the several factors: lifestyle, electric cigarette prices, and the teenager’s pocket money. Therefore, serious efforts needed to control the factors that affected the teenage users of electric cigarette. Campaign on ruthless effects of the electric cigarette among adolescents should be implemented in the school, furthermore in several places related to teenagers.